Headbangers e tererê: a experiência heavy metal na tríplice fronteira - Neves, Franciele Cristina (2014)
This dissertation is the result of a survey that aimed to understand the practices of neighboring countries that go beyond economic contact. In this sense, give emphasis on cultural exchange between Paraguay and Brazil, creating a social network well established. However, it is not any cultural contact, aboard the groups formed by the common interest in a musical genre: Heavy Metal. To accomplish it used the methodology of ethnography, in which the fieldwork lasted about a year and a half, making me present in various spaces and events held involving the group studied. At first the research was to approach the group, analyzing their identity symbolism. In a second moment, bother to analyze the production and maintenance of international social network that is created for the sake of production and consumption of musical style. In this sense, Brazilians and Paraguayans, metal fans - better known as headbangers - come to understand the boundary beyond political and geographical concepts. This group makes different uses of the border and, in moments of identification with the music, may be considered a family, becoming brothers.